Application of The Simple Additive Weighting Method in Developing Employee Assessment Decision Support System in Marketplace Company Bukalapak - Nurimansjah, Ris Akril; Rachmawaty; Malini Lubis, Fatimah; Amri; Aga Sekamdo, Muhammad (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to investigate how managers, team leaders, and supervisors can evaluate top performers with the aid of simple additive weighting in decision support systems. In this study, interviews, observation, and related literature reviews were employed as data collection techniques. This system employs fuzzy simple additive weighted (FSAW) as its approach. Two techniques, AHP and WP, were used to develop the system. Rapid Application Development, or RAD, is the system development methodology employed in this study. The findings of the study led to the following deductions: The results of this application calculation do not directly determine when assessing the best employee; you must wait for a decision from the team leader, supervisor, manager or meeting. The results provided by the best employee assessment decision support system method can be implemented using dynamic or changeable criteria to determine the best alternative. There are seven criteria used for research on evaluating the best employees in this application, namely: average process. Processes include: quantity; quality; on time; and teamwork. Productivity, which includes days in and days out/holidays. These criteria are only a basis for research in writing about the best employees, but to add or subtract criteria, you can add or subtract them in the best employee assessment application system using SAW.